Italy's fiscal crisis - Georg Erber (Intereconomics, 2011)
Italy is presently one of the most vulnerable economies in the eurozone. Over the past twenty years it has failed to adapt to increasing global competition and its public finances have deteriorated dramatically. Even with huge fiscal support from the other members of the eurozone, Italy's perspectives look rather bleak. How did this situation come about? Did Italy's EMU membership make things worse?
Keywords: 330